Evaluation of protective factors in caries free preschool children: a case-control study - Reza Yazdani; Simin Zahra Mohebbi; Maryam Fazli; Maryam Peighoun (BMC, 2020)
Abstract Background Increasing the proportion of caries-free children following the WHO's global target has led to more desirable welfare and a higher level of quality of life for children. In the present study, we aimed to evaluate the factors contributing to a caries-free condition in preschool children as a basic action towards the global goals of children's oral health. Methods This was a case-control study evaluating the protective factors contributing to dental caries free in 4-6-year-old children in Tehran/Iran in 2017. 500 preschool children and their mothers were selected from 22 randomly selected preschools and were enrolled in the study. The participants were divided into two case (caries-free) and control (with dental caries) groups. The data were collected using two data gathering tools; the child oral examination form and the mother's valid questionnaire. The latter included three domains; socio-demographic factors, behavioral oral health measures, and feeding practices and dietary habits. The criteria for caries detection were cavities in the enamel and dentine. A logistic regression model was applied to identify caries-free protective factors (P < 0.05). Results Among 230 caries-free and 270 non-caries-free children who participated in the study, boys were more caries-free (P = 0.001). The protective factors against dental caries that were identified in the study were dental check-up as the cause of dental visit, being the first child in the family, the fewer sessions night feeding of the child's, family's house ownership, and parent's university education (P < 0.05). Conclusions Dental health can be achieved by considering protective factors like the regular dental check-up and socio-economic factors. Communities are invited to pay close attention to these important protective factors as far as they can increase the proportion of caries-free among preschool children especially in countries with developing oral health care systems.